Review of 'Lélia Gonzalez: primavera para as rosas negras', by Lélia Gonzales - Gonçalves, Renata (Plural, 2019)
Referência completa:Gonzalez, Lélia. Lélia Gonzalez: primavera para as rosas negras. São Paulo: UCPA Editora, 2018.